2005
DOI: 10.1016/j.rmed.2004.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Formoterol used as needed in patients with intermittent or mild persistent asthma

Abstract: Formoterol 4.5 microg used as needed was at least as effective and safe as terbutaline 0.5 mg used as needed in intermittent and mild persistent asthma, and was associated with less systemic effects when administered as high single doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 21 publications
(22 reference statements)
1
34
0
Order By: Relevance
“…A total of 22,604 participants were randomised to eight eligible studies (Ind 2002; Jain 2004; Rabe 2006; RELIEF 2003; SD-037-0714; SD-037-0716; Tattersfield 2001; Villa 2002). The largest trial was RELIEF 2003 with 17,862 participants, whilst Rabe 2006 had 2281 participants and the remaining six trials had between 60 and 675 participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 22,604 participants were randomised to eight eligible studies (Ind 2002; Jain 2004; Rabe 2006; RELIEF 2003; SD-037-0714; SD-037-0716; Tattersfield 2001; Villa 2002). The largest trial was RELIEF 2003 with 17,862 participants, whilst Rabe 2006 had 2281 participants and the remaining six trials had between 60 and 675 participants.…”
Section: Resultsmentioning
confidence: 99%
“…The largest trial was RELIEF 2003 with 17,862 participants, whilst Rabe 2006 had 2281 participants and the remaining six trials had between 60 and 675 participants. The trials were also of different lengths with a mean duration of 29.5 weeks; three trials were 12 months long (Rabe 2006; SD-037-0714; SD-037-0716), three were six months long (Jain 2004; RELIEF 2003; Villa 2002) and two were three months long (Ind 2002; Tattersfield 2001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to albuterol use on an as‐needed basis, scheduled doses of albuterol demonstrated no benefit (Walters, Walters, & Gibson, 2002). Recent studies have reported equivocal results with use of the LABA formoterol for quick relief therapy in children (Chuchalin, Kasl, Bengtsson, Nihlen, & Rosenborg, 2005; Hermansen et al, 2006). LABA may be used to prevent EIB; however, NAEPP‐EPR3 discourages their use in this application.…”
Section: Pharmacologic Interventions: Long‐term Control Of Inflammatimentioning
confidence: 99%